Metrical invariants and covariants of couples of planes in the quasielliptic space - Rozenfeld, B. A.; Karpova, L. M.; Andreeva, L. P. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. А. Розенфельд, Л. М. Карпова, Л. П. Андреева. Метрические инварианты и коварианты пар плоскостей в квазиэллиптическом пространстве B. A. Rozenfeldas, L. M. Karpova, L. P. Andriejeva. Kvazielipsinės erdvės plokštumų dvejetų metriniai invariantai ir kovariantai